The German right, 1860-1920 : political limits of the authoritarian imagination - Retallack, James N. (German and European studies., 2006)
Written with clear, persuasive prose, this wide-ranging analysis draws together threads of reasoning from German and Anglo-American scholars over the past 30 years and points the way for future research into unexplored areas.